Factor influences on return to substance abuse in clients referred to - safari, mehdi; Mousavizade, seiedeh narjes (Advances in Nursing & Midwifery, 2015)
Background: It has been known for many years that there is a high risk of relapse after treatment of drug abuse. This has made addiction more complicated. Knowledge of related factors allows the health care professionals to initiate much broader, client centered, replace prevention strategies. Material and Methods: This is a cross sectional descriptive study that was performed on 380 clients admitted to addiction treatment center in Maraghe City, who had at least once a return to substance abuse and were selected using convenience sampling method. Data collection was performed by using structured interview and interview form in a single step. Data analysis and statistical was performed using SPSS software version 16 and ANOVA test. Results: Most cases (62/6%) had a history of leaving between 1 to 3 times. The most important factors affecting on the return to substance abuse from the perspective of clients were include: physical unpleasant symptoms of withdrawal (72/6%), feelings despair (57/3%), relationship with addict colleagues (29/5%), cheap drug prices (40/5%), low literacy (23/4%), not controlling on family (27/4%) and interaction with addict friends (57/9%). Conclusion: Various factors have a large extent influence in return to substance abuse. Therefore, in addition to eliminating the dependence of physical with drug therapy, attention to the factors that were associated with an inability to quit is important. Keywords: Return to substance abuse, Addiction treatment, Addiction